Perubahan Gaya Mencari Pasangan Melalui Aplikasi Tinder Pada Mahasiswa FISIP ULM - Situmorang, Luciandro Gideon; Zulaikha, Siti (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
The way people search for partners has changed due to technological advancements, leading to the emergence of dating apps, one of which is Tinder. This study aims to identify the factors that motivate students to use Tinder and describe the shifts in partner-seeking behaviors among students. The research uses a qualitative approach with a descriptive method. Data collection techniques include non-participatory observation, semi-structured in-depth interviews, and documentation. This study reveals several reasons that drive students to use Tinder for finding partners. First, curiosity among students indicates that curiosity, the need for validation, and the desire to build relationships are key reasons why students are interested in Tinder. Second, the ease of use highlights features like swipe and chat that facilitate partner searches based on preferences. Third, the motivation to find a partner reflects a social trend in which students are driven to explore digital spaces to avoid feeling left out, with some users explicitly using Tinder to find sexual partners. Fourth, self-branding indicates that Tinder creates a space for students to explore self-expression and openness in relationships. Lastly, increased self-confidence shows that Tinder provides students with a relaxed environment to present themselves without the immediate pressure of face-to-face interactions. Additionally, Tinder is understood as a medium that revolutionizes how students search for partners. Through Manuel Castells' network society theory, Tinder is seen as part of a digitally connected society where social and romantic relationships extend into virtual spaces. Tinder not only changes interactions but also illustrates how technology reshapes partner-seeking dynamics in modern society. The way people search for partners has changed due to technological advancements, leading to the emergence of dating apps, one of which is Tinder. This study aims to identify the factors that motivate students to use Tinder and describe the shifts in partner-seeking behaviors among students. The research uses a qualitative approach with a descriptive method. Data collection techniques include non-participatory observation, semi-structured in-depth interviews, and documentation. This study reveals several reasons that drive students to use Tinder for finding partners. First, curiosity among students indicates that curiosity, the need for validation, and the desire to build relationships are key reasons why students are interested in Tinder. Second, the ease of use highlights features like swipe and chat that facilitate partner searches based on preferences. Third, the motivation to find a partner reflects a social trend in which students are driven to explore digital spaces to avoid feeling left out, with some users explicitly using Tinder to find sexual partners. Fourth, self-branding indicates that Tinder creates a space for students to explore self-expression and openness in relationships. Lastly, increased self-confidence shows that Tinder provides students with a relaxed environment to present themselves without the immediate pressure of face-to-face interactions. Additionally, Tinder is understood as a medium that revolutionizes how students search for partners. Through Manuel Castells' network society theory, Tinder is seen as part of a digitally connected society where social and romantic relationships extend into virtual spaces. Tinder not only changes interactions but also illustrates how technology reshapes partner-seeking dynamics in modern society.